Let a ≥ b ≥ c ≥ 0 be reals such that a + b + c = 2 1 . Find the maximum value of a 2 + 3 b 2 + 5 c 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That's really interesting! I wasn't expecting 2 equality cases here.
Log in to reply
Actually there's 3 equality case, here's another one: ( a , b , c ) = ( 2 2 1 , 2 2 1 , 0 ) .
Log in to reply
Oh! I see i missed a case when c = 0 and b − a = 0 .
WAH!!!!!!! Did we miss out others?
Log in to reply
@Calvin Lin – Nope. I did the long-winded Lagrange Multiplier approach and obtained all these solutions.
Based on the condition, we can prove that f ( a , b , c ) ≤ f ( a , a , c ) or a 2 + 3 b 2 + 5 c 2 ≤ 4 a 2 + 5 c 2 Since a ≥ b ≥ c ≥ 0 and a + b + c = 2 1 . Considering f ( a , a , c ) , the condition becomes 2 a + c = 1 2 1 ⇒ c = 2 1 − 2 a ≥ 0 ⇒ a ∈ [ 7 ; 2 2 1 ] ⇒ f ( a , a , c ) = 4 a 2 + 5 ( 2 1 − 2 a ) 2 = 2 4 a 2 − 4 2 0 a + 2 2 0 5 = f ( a ) 1 We see that f ( a ) 1 m i n = 2 7 3 5 when a = 4 3 5 ∈ [ 7 ; 2 2 1 ] so now we can find the maximum by comparing f ( 7 ) with f ( 2 2 1 ) which turns out to be equal to 4 4 1 , so we have 2 equality cases ( a , b , c ) = ( 7 , 7 , 7 ) ; ( 2 2 1 , 2 2 1 , 0 )
Now I'll try to mix these variables in another way, that means f ( a , b , c ) ≤ f ( a , b , b ) . Now the condition becomes a + 2 b = 2 1 ⇒ 2 b = 2 1 − a ≥ 0 , therefore we get the interval a ∈ [ 7 ; 2 1 ] . Now we have f ( a , b , b ) = a 2 + 8 b 2 = a 2 + 2 ( 2 1 − a ) 2 = 3 a 2 − 8 4 a + 8 8 2 = f ( a ) 2 We see that f ( a ) 2 m i n = 2 9 4 when a = 1 4 ∈ [ 7 ; 2 1 ] , so the max'll be found by comparision between f ( 7 ) and f ( 2 1 ) , which also give us the same result as before. Now we have the third equality cases ( a , b , c ) = ( 2 1 ; 0 ; 0 )
From 2 methods of mixing variables, we have a 2 + 3 b 2 + 5 c 2 ≤ 4 4 1 and 3 equality cases ( a , b , c ) = ( 2 1 ; 0 ; 0 ) , ( 2 2 1 ; 2 2 1 ; 0 ) , ( 7 ; 7 ; 7 ) . @Pi Han Goh, can you check it out
Very systematic answer! +1
Very nice solution , + 1 !
why can't we have (0;0;21) as an equality case? It also satisfies the condition.
Log in to reply
because of the constrain a ≥ b ≥ c
Problem Loading...
Note Loading...
Set Loading...
Observe the following:
a 2 + 3 b 2 + 5 c 2 = a 2 + b 2 + c 2 + 2 b 2 + 2 c 2 + 2 c 2 ≤ a 2 + b 2 + c 2 + 2 a b + 2 a c + 2 b c = ( a + b + c ) 2 = 4 4 1
Thus, a 2 + 3 b 2 + 5 c 2 ≤ 4 4 1 . Equality occurs in three different cases which we shall also explore. We have
a 2 + 3 b 2 + 5 c 2 b 2 − a b + c 2 − b c + c 2 − c a b ( b − a ) + c ( c − b ) + c ( c − a ) = a 2 + b 2 + c 2 + 2 a b + 2 b c + 2 c a = 0 = 0
But we have that a ≥ b ≥ c ≥ 0 . Thus, we have b ( b − a ) ≤ 0 , c ( c − b ) ≤ 0 and c ( c − a ) ≤ 0 . From this, we must have all the terms in the sum to equal to 0. Thus, we have either a = b = c = 7 or a = 2 1 and b = c = 0 or a = b = 2 2 1 and c = 0 . Thus, we have found all solutions for equality.